IMF Survey, Volume 35, Issue 01. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 2006)
IMF cancels debt; Iraq receives new loan; Brazil and Argentina repay IMF loans; Saudi Arabia Article IV summary; Credit booms in transition economies; India's textile and clothing sector; Maghreb parliamentarians; Public awareness of economic issues.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet